PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) BERBANTU MEDIA KARTU ANGKA PERKALIAN TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SEKOLAH DASAR - Dian Nur Aisyah; Aries Tika Damayani; Siti Patonah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of the Teams Games Tournament (TGT) learning model assisted by multiplication number card media on students’ mathematical communication skills. The study was motivated by the low mathematical communication ability of third-grade students and the limited variation in the learning models applied in the classroom. The research employed a quantitative approach with a quasi-experimental method using a pretest–posttest control group design. The sample consisted of 24 students in the experimental class and 29 students in the control class. The research instrument was an essay test that had been tested for validity and reliability. Data analysis included the Shapiro–Wilk normality test, homogeneity test, and hypothesis testing using the independent samples t-test. The results showed a significant difference between the posttest scores of the experimental and control classes. The experimental class obtained an average posttest score of 86.35, while the control class scored 73.88. The hypothesis test indicated a significance value of 0.001 < 0.05, confirming a significant difference between the two classes. Analysis of each indicator revealed that although Drawing was the lowest-performing indicator, the experimental class still showed better improvement compared to the control class. The Written Text and Mathematical Expression indicators also showed consistent improvement. Therefore, it is concluded that the TGT learning model assisted by multiplication number card media has a significant effect on students’ mathematical communication skills.